#TITLE_ALTERNATIVE# - AGUS SYAMSUR RIJAL NIM: 30712007 , MUH.
Multi Drug Resistance (MDR) is a problem in cancer therapy. The main cause of resistance is the over expression of P-glycoprotein (P-gp) and its activity to cause efflux of anticancer drugs. To overcome this problem, it is necessary to use MDR inhibitors to suppress P-gp activity so that anticancer compounds can be efficiently delivered. The development of nanocarrier for anticancer can provide passive target following the Enhanced Permeation and Retention (EPR) effect so that the drug will accumulate in the tumor tissue and will be expected to decrease its toxicity in normal tissue. Some polymers/excipients include poloxamer, polyethylene glycol (PEG), D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS), Cremophor EL, Solutol HS-15, Brij-35, PeceolÃ‚Â® (glyceryl monooleate) and dendrimer have been studied could inhibit the activity of P-gp through different mechanisms but not yet known the mechanism and polymer that are most potential in inhibiting P-gp activity. It is therefore necessary to do screening study of P-gp inhibitory activity of mechanisms pathways and potent polymer in the form of nanoparticles through in vitro testing of cancer cell cultures. The purpose of this study was to investigate the most potent inhibition of P-gp activity from nanocarriers from various types of polymers/excipient as well as to produce more effective anticancer nanocarrier preparations and overcoming drug resistance by inhibiting P-gp activity. The study begins with the optimization of blank nanocarrier formation for four selected polymers ie. Synperonic PE / P84 (P84), TPGS, glyceryl monooleate (GMO) and PAMAM dendrimer G5 (PG5). The P84 and TPGS polymeric micelle nanoparticles were prepared by a thin-film hydration method of 1-10% concentration resulting in a 24-34 nm and 21-27 nm particle size range with a polydispersity index of 0.17-0.45 and 0.24-0.43. The GMO nanoparticle was prepared in liquid crystal dispersion in water or cubosomal nanoparticles. The preparation of nanoparticles was performed by ultrasonication (2.5 minutes) of GMO solution in ethanol with Poloxamer 407 (P407) in aqueous phase obtained optimum formula at 1% GMO concentration with P407 1% as stabilizer with size 108,7 nm. PG5 is a dendritic molecule that has a three-dimensional structure with an inner cavity. PG5 has a diameter of 5.4 nm. Further optimization was to prepare nanoparticles using docetaxel (DTX) as drug model gives DTX entrapment efficiency results for P84-DTX, TPGS-DTX, GMO-DTX and PG5- DTX nanoparticles 58,78 Ã‚Â± 2.03, 91,56 Ã‚Â± 7.30, 74.19 and 5.87% respectively. Characterization with photon correlation spectroscopy (PCS) for the optimized formula of each excipient resulted in a particle size of 21.8 Ã‚Â± 4.2, 29.0 Ã‚Â± 0.8, 113,8 and 14.69Ã‚Â±2.7 nm, respectively. The potential zeta was -9.06 to +22.78 mV. The morphology of each of the nanoparticle shows a spherical shape except the DTX-GMO nanoparticles that have a cubic shape tendency. In vitro cytotoxicity test in MCF7 cells by MTT method showed that P84-DTX, TPGS-DTX, GMO-DTX and PG5-DTX nanoparticles could increase the cytotoxicity of DTX 2,8; 10.8; 8.4 and 2.4 times, respectively compared to control DTX cytotoxicity. The development of MCF7 cells resistant to DTX was done by stepwise increased of DTX exposure yielding MCF7 resistant (MCF7/R) cells with IC50 value 4.7 times higher and having P-gp expression three times higher than IC50 of MCF7 parent cell. Furthermore, it is used for in vitro cancer resistance study related to the increased of P-gp expression. Visualization of P-gp expression by immunocytochemistry assay showed that treatment with P84, TPGS and PG5 nanocarrier were qualitatively decreased the number of MFC7/R cells expressing P-gp. While in the quantification test of P-gp expression using flowcytometry method,only treatment with GMO nanocarrier has been able to significantly decrease the P-gp levels. The decrease of P-gp activity by each nanocarrier was determined by multidrug resistance assay by determining the uptake of calcein-AM compound into MCF7 and MCF7/R cells. The test results showed no change in the uptake calcein-AM in MCF7 cells while in MCF7/R cells treated with GMO, PG5, P84 and TPGS nanocarrier can increase uptake calcein-AM significantly, indicating that the nanocarrier able to decrease P-gp expression. The test results also show that GMO nanocarrier have the best ability to decrease P-gp expression. At the end of this study we have produced a DTX-GMO cubosome that has a size of 100 nm, better cytotoxicity potential and can decrease P-gp expression so that it can be developed as a nanocarrier to overcome resistance to cancer therapy.